Analysis of a Transmission Gear Tooth Break - Huang Junjie; Liu Feitao; Jiang Chao; Pei Xiaorui; Li Jinming (Jixie chuandong)
Through the fracture analysis of the failure gear,finding the gear tooth broke belongs to fatigue fracture,by checking designing,assembly,material heat treatment and quality,it could be found that the insufficiency of shot peening coverage is the main reason of gear break. For this reason,according to shot peening technology specification SAE AMS- S- 13165,the shot peening again is carried out to remedy the shortage shot peening coverage,the gear strength is obviously improved,and the gear fracture is solved in bench duration test.